Environmental mitigation potential by improved nutrient managements in pear (Pyrus pyrifolia L.) orchards based on life cycle assessment: A case study in the North China Plain. (20th July 2020) - Wang, Jie; Zhang, Lihan; He, Xinhua; Zhang, Yueqiang; Wan, Yu; Duan, Shunyuan; Xu, Chenyang; Mao, Xinyu; Chen, Xinping; Shi, Xiaojun
Abstract: Despite the rapid development of intensive pear production in China, studies quantifying the environmental costs of high nutrient inputs and strategies for their mitigation are lacking. In this study, the present environmental impacts, including the reactive nitrogen losses (Nr), global warming potential (GWP), acidification potential (AP), and eutrophication potential (EP), of the pear production system in the North China Plain were addressed by survey data from 292 farmers and life cycle assessment. Moreover, environmental mitigation by groups based on quartering of the survey data and improved nutrient management scenarios based on experimental data from the study region were assessed and analyzed to explore how environmental potentials could be reduced. Results showed that the average Nr, GWP, AP, and EP values in the pear production system of the North China Plain were 5.0 kg N t −1, 372.3 kg CO2 -eq t −1, 2.4 kg SO2 -eq t −1, and 2.1 kg PO4 -eq t −1, respectively. Fertilization, especially nitrogen fertilization, was identified as the main contributor to the environmental potentials, accounting for 75% of the GWP, 89% of the AP and 95% of the EP. Quartering assessments based on the partial factor productivity of nitrogen fertilizer (PFP-N) showed a higher PFP-N and lower environmental impacts in the 1st quartile, which were mainly related to a more appropriate base fertilization ratio, higher planting density, and lower yield per tree compared to those in the other three quartiles. In addition, scenario-based assessments showed that the environmental potentials were reduced by 44–51% under the soil test and fertilization technology (STF) scenario and 51–56% under the nutrient expert fertilizer recommendation (NE) scenario compared to the Mean scenario (all 292 farmers) in the field experiments. In addition, the integrated nutrient-orchard management strategies under the high-yield and high-PFP-N (HH) scenario could significantly further mitigate the environmental impacts. Results from this study thus provide possible strategies for obtaining a sustainable pear industry to pear orchard managers and policy makers. Highlights: High environmental risk exists in the pear production systems of North China Plain. Chemical nitrogen fertilization contributes 75–95% to environmental potentials. Good farming practices improved the PFP-N and lowered environmental impacts. Improved fertilizer recommendations reduced environmental impacts by 44–56%.